The Use of Course Review Horray (CRH) Strategy to Promote Students' Self-Confidence in Learning Vocabulary - Kamarudin Kamarudin; Tawali Tawali; Muhammad Muhlisin (EDULANGUE, 2018)
This research aims at finding out whether Course Review Horray strategy has effect to promote students’ self-confidence in learning vocabulary at the seventh grade students of MA NW Senyiur Keruak Lotim or not. This research rises since the use of English vocabulary plays crucial roles of mastering English language. Students will gain a huge number of benefits in which they can cope with various vocabulary items. For instance; students will automatically convince their self to speak up fluently where they know much of variety of vocabulary. This phenomenon comes up along with students of MA NW Senyiur Keruak Lotim. This research was a quasi-experimental with two group pre-test and post-test design. The population was all the students of the seventh grade at MA NW Senyiur Keruak Lotim consisted of 74 students from 3 classes. The samples of this research were 2 classes consisted of 25 students each group. The experimental group was treated by using Course Review Horray strategy and control group was using Engage Study and Activate Strategy. The instruments of collecting the data were vocabulary test and questionnaire. After the data analysis completed, it was found that the questionnaire of students’ percentage was 56% the students got qualification A as criteria Student master 90%-100% of all indicators, 24% students get qualification as B master 80%-89% of all indicators, 16% students get qualification as C master 65%-79% of all indicators, 4% students get qualification as D master 55%-64% and 0% students got qualification as E master 0%-54% of all indicators. The number of T-test score was (2.865) > T-table (2.011). So, Course Review Horray (CRH) has effect towards students’ self-condident in learning English vocabulary